Higher-order anharmonicity leads to ultra-low thermal conductivity and high output power density of SnTe-based thermoelectric materials and modules. (September 2022) - Wang, Teng; Dou, Kunpeng; Wang, Hongchao; Kim, Jiyong; Wang, Xue; Su, Wenbin; Chen, Tingting; Kim, Woochul; Wang, Chunlei
Abstract: Higher-order anharmonicity is found in copper and manganese doped tin telluride (SnTe) alloys, and its effect on thermoelectric performance is systematically studied. Analyzation of thermal expansion shows that the ionic potential not only consists of cubic term, but also quartic term. Short phonon lifetime derived from more diffused peak of Brillouin spectrometer results from the higher-order anharmonicity. As a result, an ultra-low lattice thermal conductivity of 0.5 Wm −1 K −1 is achieved. Soft optical phonon mode was observed from Raman spectrometer, the transverse optical - longitudinal acoustic phonon interaction may be the reason for the enhanced anharmonicity. Combining with the enlarged power factor caused by band convergence, the highest figure of merit reaches 1.3 at 873 K for doped samples. Additionally, the large temperature difference of 600 K and high output power densities of 291 mWmm −3 of simulated SnTe uni-leg module are achieved. This work supplies way for revealing the anharmonicity experimentally, and proves modification of intrinsic anharmonicity is an avenue for enhancing the thermoelectric performance of SnTe alloys. Graphical abstract: Image 1 Highlights: Quartic an-harmonic term plays an important role for Cu/Mn doped SnTe samples. Enhanced anharmonicity results in short phonon lifetime and ultra-low κL . A maximum figure of merit 1.3 is achieved. Maximum hot side temperature difference and output power density are increased.